2022
DOI: 10.1155/2022/9179427
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Ameliorates Hypoxic Pulmonary Hypertension via Suppression of Oxidative Stress

Abstract: Hypoxic pulmonary hypertension (HPH) is a progressive cardiopulmonary system disease characterized by pulmonary vascular remodeling. Its occurrence and progression are closely related to oxidative stress. Lycopene, extracted from red vegetables and fruits, exhibits a particularly high antioxidant capacity that is beneficial for cardiovascular diseases. Nevertheless, the role and mechanism of lycopene in HPH remain unknown. Here, we found that lycopene reversed the elevated right ventricular systolic pressure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…NLRP3 detects high ROS concentrations, which encourages the NLRP3 inflammasome's development and activation. Furthermore, TNF-α is essential for the activation of caspase-1 [27]. All of these factors can enhance pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLRP3 detects high ROS concentrations, which encourages the NLRP3 inflammasome's development and activation. Furthermore, TNF-α is essential for the activation of caspase-1 [27]. All of these factors can enhance pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have demonstrated that this dose is effective in producing antioxidant defence and reducing the toxicity of certain xenobiotics [19][20][21][22][23][24]. -Group III: Rats were treated with IMI at a dose of 45 mg/kg, which is 1/10 of the LD50 [25][26][27]. -Group IV: Rats were treated with a combination of IMI (45 mg/kg) and LYC (10 mg/kg).…”
Section: Experimental Designmentioning
confidence: 99%